How modern-day traditional healers diagnose and treat cancer : the case of Malaysia. - Sharan, Merriam; Muhamad, Mazanah (2011)
Traditional healers are so embedded in the Malay culture that they are often the first and sometimes only source of healthcare even for chronic diseases such as cancer. Our qualitative study was designed to uncover how Malay traditional healers diagnose and treat cancer. Further, we wanted to ascertain their willingness to work with the allopathic system in relieving the cancer burden in Malaysia. Interviews with 14 Malay traditional healers revealed a wide variety of diagnostic and treatment practices, and there is a range of receptiveness for working with the Western medical system with Islamic healers being the most receptive.